Response and Recovery Times of Elastic and Viscoelastic Capsules in Shear Flow. (3rd June 2015) - Gounley, John; Peng, Yan
Abstract Amid the recent interest in the role of membrane viscosity in the deformation of a fluid-filled capsule, we consider the role of various capsule properties (shear elasticity, membrane bending stiffness and viscosity) in determining the response and recovery times of a spherical capsule in shear flow. These times are determined by fitting exponential functions to results for the Taylor deformation parameter Dxy. We focus on the relationship between the membrane and fluid viscosity ratios, as suggested by Diaz et al, and whether adjustments to the fluid viscosity ratio may be used to approximate the effects of membrane viscosity. Based on its ability to reproduce response and recovery times, our results suggest that such an approach holds promise.